Home is where the head is: a distributed cognition account of personal health information management in the home among those with chronic illness. Issue 8 (3rd August 2018) - Werner, Nicole E.; Jolliff, Anna F.; Casper, Gail; Martell, Thomas; Ponto, Kevin
Abstract: Managing chronic illness requires personal health information management (PHIM) to be performed by lay individuals. Paramount to understanding the PHIM process is understanding the sociotechnical system in which it frequently occurs: the home environment. We combined distributed cognition theory and the patient work system model to investigate how characteristics of the home interact with the cognitive work of PHIM. We used a 3D virtual reality CAVE that enabled participants who had been diagnosed with diabetes ( N = 20) to describe how they would perform PHIM in the home context. We found that PHIM is distinctly cognitive work, and rarely performed 'in the head'. Rather, features of the physical environment, tasks, people, and tools and technologies present, continuously shape and are shaped by the PHIM process. We suggest that approaches in which the individual (sans context) is considered the relevant unit of analysis overlook the pivotal role of the environment in shaping PHIM. Practitioner Summary: We examined how Personal Health Information Management (PHIM) is performed in the homes of diabetic patients. We found that approaches to studying cognition that focus on the individual, to the exclusion of their context, overlook the pivotal role of environmental, social, and technological features in shaping PHIM.